Association of C1q/TNF-related protein-9 (CTRP9) level with obstructive sleep apnea in patients with coronary artery disease. (25th November 2020) - Wang, X; Li, Z; Du, Y; Jia, L; Fan, J; Guo, R; Ma, X; Nie, S; Wei, Y
Abstract: Background: Obstructive sleep apnea (OSA) is closely related to the incidence and progression of coronary artery disease (CAD), but the mechanisms linking OSA and CAD are unclear. C1q/TNF-related protein-9 (CTRP9) is a novel adipokine that protects the heart against ischemic injury and ameliorates cardiac remodeling. Purpose: We aimed to ascertain the clinical relevance of CTRP9 with OSA prevalence in patients with CAD. Methods: From August 2016 to March 2019, consecutive eligible patients with CAD (n=154; angina pectoris, n=88; acute myocardial infarction [AMI], n=66) underwent cardiorespiratory polygraphy during hospitalization. OSA was defined as an apnea-hypopnea index (AHI) ≥15 events h –1 . Plasma CTRP9 concentrations were measured by ELISA method. Results: OSA was present in 89 patients (57.8%). CTRP9 levels were significantly decreased in the OSA group than in the non-OSA group (4.7 [4.1–5.2] ng/mL vs. 4.9 [4.4–6.0] ng/mL, P=0.003). The difference between groups was only observed in patients with AMI (3.0 [2.3–4.9] vs. 4.5 [3.2–7.9], P=0.009), but not in patients with AP (5.0 [4.7–5.3] ng/mL vs. 5.1 [4.7–5.9] ng/mL, P=0.571) (Figure 1). Correlation analysis showed that CTRP9 levels were negatively correlated with AHI (r=−0.238, P=0.003) and oxygen desaturation index (r=−0.234, P=0.004), and positively correlated with left ventricular ejection fraction (r=0.251, P=0.004) in all subjects. Multivariate analysis showed that male gender (OR 3.099, 95% CI 1.029–9.330, P=0.044), body mass index (OR 1.148, 95% CI 1.040–1.268, P=0.006), and CTRP9 levels (OR 0.726, 95% CI 0.592–0.890, P=0.002) were independently associated with the prevalence of OSA. Conclusions: Plasma CTRP9 levels were independently related to the prevalence of OSA in patients with CAD, suggesting that CTRP9 might play a role in the pathogenesis of CAD exacerbated by OSA. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Natural Science Foundation of China